2016
DOI: 10.1128/jvi.01593-16
|View full text |Cite
|
Sign up to set email alerts
|

Feline Immunodeficiency Virus Vif N-Terminal Residues Selectively Counteract Feline APOBEC3s

Abstract: Feline immunodeficiency virus (FIV)Vif

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 81 publications
2
11
0
Order By: Relevance
“…The results showed that FIV Vif efficiently degraded all three tested feline A3s (Felis catus A3Z2b [FcaA3Z2b], FcaA3Z3, and FcaA3Z2bZ3) in the absence of DN-CUL5 ( Fig. 1B), which is consistent with data from previous studies (4,11,14). The presence of DN-CUL5 enhanced the cellular protein level of Vif and abolished the degradation of the A3s (Fig.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The results showed that FIV Vif efficiently degraded all three tested feline A3s (Felis catus A3Z2b [FcaA3Z2b], FcaA3Z3, and FcaA3Z2bZ3) in the absence of DN-CUL5 ( Fig. 1B), which is consistent with data from previous studies (4,11,14). The presence of DN-CUL5 enhanced the cellular protein level of Vif and abolished the degradation of the A3s (Fig.…”
supporting
confidence: 91%
“…Feline CUL5 and human CUL5 differ in only one amino acid, and this mutation does not affect its interaction with FIV Vif (18). It was also shown that FIV Vif can induce the degradation of feline A3s in both feline kidney CRFK and HEK293T cells, thus supporting that FIV Vif can interact with human and feline CUL5 proteins (11,18). In this study, we first identified that three FIV Vif N-terminal mutants (53FI54, 57LR58, and 77VRE79) partially lost CUL5 binding, compared to wild-type FIV Vif (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Feline tetherin can prevent the release of FIV and HIV-1, which is antagonized by the FIV envelope glycoprotein [ 41 , 42 , 43 ]. Feline APOBEC3 (A3) restricts the infectivity of Vif-deficient FIV (FIVΔVif), and FIV Vif counteracts the feline A3 antiviral activity [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%